Herpesvirus glycoproteins undergo multiple antigenic changes before membrane fusion. - Daniel L Glauser; Anne-Sophie Kratz; Philip G Stevenson (PLoS ONE)
Herpesvirus entry is a complicated process involving multiple virion glycoproteins and culminating in membrane fusion. Glycoprotein conformation changes are likely to play key roles. Studies of recombinant glycoproteins have revealed some structural features of the virion fusion machinery. However, how the virion glycoproteins change during infection remains unclear. Here using conformation-specific monoclonal antibodies we show in situ that each component of the Murid Herpesvirus-4 (MuHV-4) entry machinery--gB, gH/gL and gp150--changes in antigenicity before tegument protein release begins. Further changes then occurred upon actual membrane fusion. Thus virions revealed their final fusogenic form only in late endosomes. The substantial antigenic differences between this form and that of extracellular virions suggested that antibodies have only a limited opportunity to block virion membrane fusion.